الوجودية الإسلامية أو المنظور الإسلامي للزمن قراءة في الرؤية الفكرية للأديب محمود المسعدي - زاغز, شهرزاد (University of Eloued جامعة الوادي, 2009)
قمنا في هذا العمل بدراسة الزمن وذلك من خلال إبراز صراع الإنسان مع الزمن وفق الرؤية الإسلامية للزمن حيث الإيمان بامتداده إلى وجود آخر أبدي ، مثلما يبرز بنفس الإيمان تشتت الإنسان بين نوازع مختلفة..ولإبراز حدّة الصراع بين الهاجسين سوف نركّز على فلسفة الزمن من خلال وجهة نظر محمود المسعدي، وتحديدا في ما أسميناه بالوجودية الإسلامية.. In this work, we studied time by demonstrating Man’s conflict with time according to the Islamic vision to time with the belief in its extension to another permanent existence. In the same faith appears Man’s distortion between different motives/ desires. To show the fierce conflict between both anxieties, we will concentrate on the philosophy of time in Mahmoud El Massaadi view , mainly in what is called Islamic existentialism.
Keywords: الرؤية الإسلامية، الزمن، محمود المسعدي; Islamic vision, time, Mahmoud El Massaadi